Concurrent granulomatous mastitis and invasive ductal cancer in contralateral breasts—a case report and review. Issue 12 (7th December 2021) - Evans, Jonathan; Sisk, Louis; Chi, Kee; Brown, Shaun; To, Henry
Abstract: Idiopathic granulomatous mastitis (GM) is an uncommon chronic benign disease of the breast that is challenging to clinically distinguish from malignancy. However, it is unusual to diagnose GM concurrently with carcinoma in the same breast and rarer still to encounter GM and malignancy in contralateral breasts. We describe the case of a 39-year-old female who presented with right multifocal breast cancer and left granulomatous mastitis, discuss complexities in her management plan and review the literature on this unusual concurrent condition.